El uso de herramientas gamificadas en el aula de clases. - Albuja, Mónica (2022)
Multiple studies show the deficiencies of teachers in the use and management of gamified technological tools, despite the advancement of technologies that facilitates the teachinglearning process, they are not used by teachers in the classroom, because they are not familiar with the pedagogical use of them to develop creativity and the acquisition of new knowledge and obtain favorable academic results. Another unfavorable point is that the teacher does not recognize video games to arouse the interest of students in their meaningful learning. This situation occurs in institutions in Ecuador. Hence, the objective of this study is to verify the use of gamified tools in the classroom as a support for teaching. To achieve this objective, a quantitative route was followed and the data collection technique was a Likert-type survey that measured access to electronic devices and use of technology; creativity in the use of video games for teaching; communication between teachers in the practice of video games for teaching; teacher training in gamification for teaching. A questionnaire was applied through Google Forms to 23 teachers from two educational institutions at the basic elementary level. The data was analyzed using the Excel program. Among the main findings, the lack of use and creation of video games for teaching is significant, therefore, this does not become a unique and significant experience for students.